Recruitment of the stalked barnacle Pollicipes pollicipes on an artificial substratum ("barticle") and transfer to an extensive system of production: sucess techniques and pitfalls - Fernandes, Joana Isabel Rodrigues Nascimento (2019)
Aquaculture potential of the stalked barnacle Pollicipes pollicipes was investigated. Artificial collectors (barticles) of larvae and juveniles were deployed at the Cape of Sines and later transferred to a floating platform in the Port of Sines for juvenile growth. Survival and growth data and/or practical issues, justified the choice of the mid shore as the most suitable barticles’s deployment level in the field, and of plates within individual cages as the best option of the analysed growing conditions in the platform. Survival of barnacles transferred to the platform was initially high but decreased to zero over time due to intense biofouling. During winter, growth in the platform was higher than in the Cape of Sines. Barnacles’ survival and growth rate during winter in the platform are promising results, although biofouling, namely in spring and summer, is still a major problem to address; Resumo: Este estudo analisou o potencial da aquacultura do percebe Pollicipes pollicipes. Usaram-‐se coletores artificiais de larvas (“barticles”) colocados no Cabo de Sines (SW Portugal) que foram posteriormente transferidos para uma plataforma flutuante no Porto de Sines para crescimento dos juvenis. Com base nos dados de sobrevivência e crescimento obtidos e/ou aspetos práticos, o nível intertidal médio foi considerado como o mais adequado para a colocação dos “barticles”, e as placas em redes individuais como a melhor opção para o crescimento dos percebes na plataforma. A sobrevivência dos percebes transferidos foi alta inicialmente, mas decresceu ao longo do tempo para zero, devido a “biofouling” intenso. Durante o inverno, o crescimento foi superior na plataforma relativamente ao Cabo de Sines. A sobrevivência e a taxa de crescimento dos percebes na plataforma durante o inverno constituem resultados promissores, embora o “biofouling”, nomeadamente na primavera/verão, seja ainda um problema que deverá ser mitigado futuramente.